What Psychology Teachers Should Know About Open Science and the New Statistics. (April 2020) - Morling, Beth; Calin-Jageman, Robert J.
Psychology teachers have likely heard about the "replication crisis" and the "open science movement" in psychology, and they are probably aware that psychologists have proposed new standards for research practice. How should our psychology courses reflect these new standards? We describe several modern practices that have transformed our field and that seem likely to endure: preregistration of studies, transparency of reporting, norms for replication, and the new statistical focus on estimation and precision. We offer suggestions for how to integrate these new practices into psychology courses.